Implementasi Strategi Marketing Dakwah pada Media Kontemporer - Sofyan Rizal (STID DI AL-HIKMAH, 2016)
This study aimed to explore the formulation of marketing strategies for da’wah to see how the implementation of the marketing done by the perpetrators of da’wah on television and then formulate and formulate an appropriate marketing strategy for da’wah, especially propaganda by using contemporary mass media. The method used is descriptive method of analysis with a qualitative approach. In conclusion, Events mamah and Aa special segment, while Islam was a beautiful occasion wear segment which is more common, but it's working on all segments with an appropriate approach. Two of the show has also done well targeting, as a continuation of the strategy of segmentation, ie by applying a variety of ways that berdeda devoted to each segment. Positioning is also done with the uniqueness and the uniqueness communicate with a more simple and communicative. Differentiation reached by strengthening the personnel and the image that is different from other similar events.